Three essays on the relationship between emotions and financial resources - Enete, Shane (Kansas State University, 2020)
This three-essay dissertation investigated the relationship between emotions and financial resources using a convenience sample of 993 U.S. adults. The broaden and build theory was used in order to predict that emotions help explain variation in the financial resources of U.S. households. Essay one found that emotions were associated with financial resources after controlling for traditional demographic predictors using an ordered logit model. Essay two found that emotions were associated with financial time horizon after controlling for traditional demographic predictors using a structural equation modeling approach. Finally, essay three found that financial time horizon served as a mechanism for helping explain the relationship between emotions and financial resources using a structural equation modeling approach. Results suggest that policymakers, financial professionals, and academics should include emotions as a predictor of financial resources. In addition, future financial positive psychology interventions should use financial time horizon as an important mechanism that may help strengthen the relationship between emotions and financial resources indirectly.
Keywords: Positive psychology; Finance; Emotions